2021
DOI: 10.3389/fpls.2021.674470
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic, Physiological and Genetic Changes Associated With Evolution, Migration and Modern Breeding in Durum Wheat

Abstract: A panel of 172 Mediterranean durum wheat landraces and 200 modern cultivars was phenotyped during three years for 21 agronomic and physiological traits and genotyped with 46,161 DArTseq markers. Modern cultivars showed greater yield, number of grains per spike (NGS) and harvest index (HI), but similar number of spikes per unit area (NS) and grain weight than the landraces. Modern cultivars had earlier heading but longer heading-anthesis and grain-filling periods than the landraces. They had greater RUE (Radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 83 publications
(126 reference statements)
0
19
0
Order By: Relevance
“…Grain weight showed the opposite pattern, suggesting that under drier and hotter conditions, cultivars filled their grains at a higher rate (1.29 g/day in 2017 and 1.06 g/day in 2016 and 2018), thus showing a shorter grain filling duration (GFD) in 2017. The high yields recorded, considering the rainfed conditions of the field trials, could be attributed to the high soil fertility (~3% of organic matter) and the superficial subsoil water layer at this site (Royo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Grain weight showed the opposite pattern, suggesting that under drier and hotter conditions, cultivars filled their grains at a higher rate (1.29 g/day in 2017 and 1.06 g/day in 2016 and 2018), thus showing a shorter grain filling duration (GFD) in 2017. The high yields recorded, considering the rainfed conditions of the field trials, could be attributed to the high soil fertility (~3% of organic matter) and the superficial subsoil water layer at this site (Royo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…Landraces from SP2 are better adapted to colder and wetter environments than landraces originating in the southern part of the Mediterranean basin. This adaptation pattern has been associated with the greatest early soil coverage and more aboveground biomass along the whole cycle length (Royo et al, 2014 , 2021 ). For this reason, the canopy remains green much longer in landraces from the northern Mediterranean countries than in those from the southern Mediterranean countries (Royo et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that durum wheat landraces are a valuable source of resistance alleles against fungal pathogens [ 8 , 12 , 29 31 ]. STB resistance sources on durum wheat were identified in many countries such as Tunisia [ 12 ], Ethiopia [ 8 ], Iran [ 32 ] and Spain [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Grain weight showed the opposite pattern, suggesting that under drier and hotter conditions, cultivars filled their grains at a higher rate (1.29 g/day in 2017 and 1.06 g/day in 2016 and 2018), thus showing a shorter GFD in 2017. The high yields recorded, considering the rainfed conditions of the field trials, could be attributed to the high soil fertility (approximately 3% of organic matter) and the superficial subsoil water layer at this site (Royo et al 2021).…”
Section: Phenotypic Performancementioning
confidence: 84%
“…Landraces from SP2 are better adapted to colder and wetter environments than landraces originating in the southern part of the Mediterranean basin. This adaptation pattern has been associated with the greatest early soil coverage and more aboveground biomass along the whole cycle length (Royo et al 2014(Royo et al , 2021. For this reason, the canopy remains green much longer in landraces from northern Mediterranean countries than in those from southern Mediterranean countries (Royo et al 2014).…”
Section: Phenotypic Performancementioning
confidence: 99%